2019
DOI: 10.1108/ijrdm-08-2018-0157
|View full text |Cite
|
Sign up to set email alerts
|

Advertising music: an alternative atmospheric stimulus to retail music

Abstract: Purpose Studying the role of advertising music (ad music) in a retail context can be an emergence of new marketing practices. The purpose of this paper is to identify the potential usage and utility of ad music as an atmospheric stimulus in contrast to music (retail music) as an atmospheric stimulus. This paper also aims to provide a model, which depicts how ad music could be an alternative to retail music in retail settings with regard to consumers’ attitudinal influence and its optimistic correlation with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 79 publications
(213 reference statements)
1
9
0
1
Order By: Relevance
“…Melody, soft music and instrumental music in the background are the three most preferred types of music in the background. Thus, this confirms the recent study of the experimental work of Yi and Kang (2019) and Washim et al. (2019), who reported that retail consumers have the lowest satisfaction and behave in the most arousing and dominating ways in no music setting as compared to foreground, and background music settings (Yi and Kang, 2019, p. 411).…”
Section: Resultssupporting
confidence: 90%
“…Melody, soft music and instrumental music in the background are the three most preferred types of music in the background. Thus, this confirms the recent study of the experimental work of Yi and Kang (2019) and Washim et al. (2019), who reported that retail consumers have the lowest satisfaction and behave in the most arousing and dominating ways in no music setting as compared to foreground, and background music settings (Yi and Kang, 2019, p. 411).…”
Section: Resultssupporting
confidence: 90%
“…In this regard, the diffusion of music and its reception by listeners via the Internet and other specific networks is highly shaped by the direct and indirect advertising of all kinds of products and services, and by related economic interests (Frigkas et al, 2008; Rau & Chen, 2006). Hence, the networks do not tend to spread a musical culture based on quality, but rather on the potential sales to cybernauts from advertising messages disseminated by the tech companies that run them (Raja et al, 2019; Ruth & Spangardt, 2017). Thus, messages of a musical nature succumb to the uniformity and banality of much of the content generally distributed by the audio-visual media (Bobo, 2005), squandering the networks’ excellent potential for the transmission of musical content oriented towards educating users and providing them with high-quality entertainment.…”
Section: Music and The Mediamentioning
confidence: 99%
“…En este sentido, la difusión de la música y su recepción por parte de los oyentes a través de Internet y de otras redes concretas están determinadas en gran medida por la publicidad directa e indirecta de todo tipo de productos y servicios, y por intereses económicos relacionados (Frigkas et al, 2008; Rau & Chen, 2006). Por tanto, las redes no tienden a divulgar una cultura musical basada en la calidad sino en el potencial de ventas a los cibernautas de mensajes publicitarios difundidos por las compañías tecnológicas que las gestionan (Raja et al, 2019; Ruth & Spangardt, 2017). En consecuencia, los mensajes de carácter musical son víctima de la uniformidad y banalidad de gran parte del contenido que suelen difundir los medios audiovisuales (Bobo, 2005), que desperdician el excelente potencial de las redes para transmitir contenidos musicales orientados a educar a los usuarios y a facilitarles un entretenimiento de alta calidad.…”
Section: La Música Y Los Medios De Comunicaciónunclassified
“…Music has been found to influence experience, meaning that enjoyable music enhances pleasurable feelings for customers (Triantafillidou et al, 2017). The use of music is effective in retailing and advertising (Raja et al, 2019). Playing the right music can assist retail stores in developing a good and acceptable atmosphere, which contributes to the store's image and the type of consumers that visit it (de Farias et al, 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Playing the right music can assist retail stores in developing a good and acceptable atmosphere, which contributes to the store's image and the type of consumers that visit it (de Farias et al, 2014). According to Raja et al (2019), consumers are likely to experience three emotional states in a retail environment, pleasure (satisfaction), arousal (stimulation), and dominance (feeling in charge), which may or not determine the time spent in-store and purchasing decisions. Another critical element in the physical store environment is lighting.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%